ABOUT THE GLOBALIZATION OF THE DIGITAL EDUCATIONAL ENVIRONMENT - Balykbaev, Т.О.; Bidajbekov, Е.Ы.; Grinshkun, В.В. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2024)
The article discusses the factors that are important for the integration and unification of disparate digital resources within a single environment. The expediency and possibility of building such environments is emphasized not only within the framework of informatization of individual educational organizations, but also within the framework of globalization of educational systems, which is significant for strengthening cross-border education, including in the Turkic-speaking community.